Pelatihan Pembelajaran Berbasis Games (Gamifikasi) bagi Guru-Guru SD di Desa Cisaat Kecamatan Ciater Kabupaten Subang - Safitri, Dini; Rusdi, Rusdi; Pusparini, Fitria (Universitas Nusantara PGRI Kediri, 2025)
The Digital/Non-Digital Game-Based Learning (Gamification) training for elementary school teachers in Cisaat Village, Ciater District, Subang Regency, aims to improve teachers' understanding and skills in implementing innovative learning methods. Social Sciences learning is often considered boring due to a lack of interactivity, necessitating a new approach using games to improve student motivation and learning outcomes. This activity involved training conducted on June 25-26, 2024, using a tutorial method that included preparation, implementation, and evaluation. Through pretests and posttests, the evaluation showed a significant increase in participants' understanding of game-based learning. The questionnaire results showed a high level of participant satisfaction with the material presented and enthusiasm for implementing new techniques in learning. Thus, this training successfully enriched teachers' creativity and provided solutions to improve the quality of learning at the elementary school level.